Development of a Smartphone Application for Safe Car Driving Using Google API and Built-in Sensor - Tuan Nguyen, Khai; Van Pham, Thanh; Nguyen, Van Dung; Thanh Do, Long; Tran, An-Van; Tran, Duc-Tan (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In the world where streets brimmed with vehicles are no longer an foreign sight, vehicle accidents come along as one of unwanted consequences. Accidents are due to many reasons, though however the reason is, most of the times it leads to damaged vehicle(s), injuries or even fatality. In this research, we present Car Safe, a smartphone application which can make phone call reception decision, text readout to prevent distraction, driving time alert and send the location of the driver upon the occurrence of a detected crash. While the Google Activity Recognition API only detects driving state approximately 89% of the time, our proposed method yields more than 93% detection.